Dental Health Education Using Demonstration and Videos on Students’ Toothbrushing Behavior Changes at SDS Al- Azhar Bukittinggi - Aljufri; Sriani, Yustina; Yuzar, Yessi; Yenti, Aflinda; Rosmalia, Dewi (POLTEKKES KEMENKES PADANG, 2023)
Dental health education is one of the programs to tackle dental health problems in Indonesia. The selection of the appropriate method in delivering educational material significantly contributes to the achievement of the targeted behavior change. Demonstration is one of the methods commonly used in this process. The demonstration method can be amplified by incorporating audio-visual media. It can be used to deliver the material more interestingly so that learning can be more interactive. This study aims to determine dental health education using demonstrations and videos on toothbrushing behavior changes among primary school students aged 9-12 years old. This research is quasi-experimental with Pretest-Posttest Group Design. The research samples are students aged 9-12 years old at SDS Al-Azhar Bukittinggi with a total number of 100 students. These samples were collected by simple random sampling. The research procedure started by giving a pre-test followed by a demonstration and video presentation about toothbrushing for different groups. The research then ended with a post-test to find out tooth brushing behavior. The data were analyzed using Wilcoxon and Mann-Whitney test. From the results of the Wilcoxon test, dental health education with demonstration method and video before and after the treatment obtained a significance value of 0.000 <0.05. It indicates that dental health education with demonstrationmethod and video effectively improves the respondent's toothbrushing behavior. The Mann-Whitney test showed a significance value of 0.000 < 0.05. It indicates that there is a difference in toothbrushing behavior between the demonstration method and video. Dental health education with the demonstration method is more effective in changing the respondent's toothbrushing behavior. Therefore, it is recommended for school teachers and UKGS officers to conduct dental health education using the demonstration method to change the toothbrushing behavior of elementary school students.